Dynamic networks in early international agrobusiness - Méndez Lazarte, Christiam Ismael (2019)
This research aims to understand the benefits of networks, based on their origin, for the process of companies’ accelerated internationalization. The study adopts as a reference the emergence of Born Global enterprises, International New Ventures (INV), and the Networking approach. An inductive and interpretative method was applied, using in-depth interviews, triangulated with public documents about the studied companies. The research analyzed two companies oriented to international markets since their establishment. The interviews’ transcripts were analyzed using matrices elaborated throughout the study, which were interrelated with the elements of early international business, identified in the interviewees’ responses. The analysis allowed the development of a chronology of the cases, and the networks’ origin, benefits, and strategies related to the accelerated internationalization model were identified. The results showed a diverse typology of networks by origin: family, previous work experience, academic (Undergraduate and Graduate), events, institutional (public and private), and partners. These networks promote the process of accelerated internationalization with: contacts, emotional support, knowledge (lessons, experiences, among others), resources (monetary and non-monetary), forming teams and networking, which are elements of the Born Global and INV companies. The research concludes that the scenario of products with low local demand and niches in the international markets form an appropriate context for the emergence of Born Global or INVs, and that networks in the first stage (even before the companies foundation) guide the internationalization strategies. These strategies support the growth and evolution of networks the company is connected to throughout its development process.